Effect of air pollution on marathon running performance - Marr, L. C.; Ely, M. R. (Medicine & Science in Sports & Exercise, 2010)
Before the 2008 Olympic Games, there was concern that air pollution in Beijing would affect the performance of marathon runners. Air pollutant concentrations during marathon running and their effect on performance have not been reported. Evidence suggests that the lung function of females may be more susceptible than that of males to air pollution, but it is uncertain if this translates to decreased marathon performance.